Less is More? Exploring the Impact of Scaled-Down Network Telescopes on Security and Research - Camargo, Arthur V. C.; Bertholdo, Leandro M.; Granville, Lisandro Zambenedetti (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2024: Anais do XLII Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc.2024.1538, 2024)
Cyber threat intelligence relies on network telescopes for detecting attack, and emerging threats, traditionally utilizing a substantial portion of the IPv4 address space. However, the escalating scarcity and value of this resource force universities and companies to grapple with the challenge of re-purposing their address spaces, potentially impacting cybersecurity effectiveness and hindering research efforts. In this paper we investigate the historical usage of IPv4 addressing space in network telescopes and explores the impact of reducing this space on their ability to identify attackers and collect valuable research data. Our findings reveal that even halving the allocated space for a network telescope may still permits the detection of 80% of unique cyber attack sources, and the address allocation schema have low influence in this detection.